INTERNATIONAL MULTICENTER EXPERIENCE IN THE TREATMENT OF INVASIVE ASPERGILLOSIS IN IMMUNOCOMPROMISED CANCER PATIENTS - R. Hachem; Marjorie Batista; Souha S Kanj; Saaed El Zein; Sara Haddad; Ying Jiang; Nobuyoshi Mori; Rocha Vanderson; Anne-Marie Chaftari; Issam I Raad (Mediterranean Journal of Hematology and Infectious Diseases, 2019)
BACKGROUND: Invasive aspergillosis (IA) is a life-threatening infection in immunocompromised patients. In this study, we compared the efficacy of voriconazole containing regimen vs non-voriconazole containing regimen in patients with IA.